(untitled) (Journal of Bangladesh Academy of Sciences, 2019)
Four soil fungi were isolated from the soil by serial dilution and were identified as Aspergillus flavus Link, A. fumigatus Fresenius, A. niger van Tieghem and Trichoderma viride Pers. The soil fungi were selected to evaluate their antagonistic potential against seed borne fungus Fusarium merismoides isolated from sesame. In dual culture colony interaction Trichoderma viride showed the highest (45.88%) growth inhibiting effect on F. merismoides followed by A. niger (40.00%), A. flavus (36.37) and A. fumigatus (30.77%). Volatile metabolites from T. viride showed the highest growth inhibiting effect on F. merismoides (67.69%) and non-volatile metabolites from T. viride showed the highest growth inhibiting effect on F. merismoides (75.00%). Journal of Bangladesh Academy of Sciences, Vol. 43, No. 1, 17-23, 2019